Hubungan faktor budaya organisasi sekolah dengan kepuasan kerja di kalangan guru sekolah menengah kebangsaan zon A, Bahagian Kuching/Samarahan - Hasan Al-Banna, Bin Mohamed. (2001)
The purpose of this study was to find out the relationship between the organisational culture of school factor and the job satisfaction among the secondary school teachers. Hence, this study was carried out with its main purpose to study the level of job satisfaction among school teachers and their satisfaction level towards the school organisation culture.